ENHANCING THE SERIOUS ABILITY OF USE OF PINK TOWER LAYOUTS IN CHILDREN AGED 4-5 YEARS AT SRI LESTARI PAUD AT PONTANG - Defita Erimedia, Eneng Sri Susilawati, Hadi Sutiawan (Jurnal Pendidikan dan Penelitian Serumpun Mendidik, 2025)
This research aims to 1) To find out if using a pink tower arrangement medium can improve the seriesing ability. 2) To know how the Pink tower beam is simulated against the 4 - 5 year old children's seriesing abilities in PAUD Sri Lestari Kec. Pontang. Guide I: Dr. Eneng Sri Susilawati, M.Pd. Guide II: Hadi Sutiawan, MD, University of Buddhist Faithfulness (USB) Rangkasbitung 2024. This type of research is collaborative classroom action research. Each cycle consists of four stages: planning, implementation, observation and reflection. The subject of this study is the age of 4-5 years in the PAUD Sri Lestari district of Pontang with a total of 15 children. The object of the research is the ability to serialize through the pink tower arrangement beams. The data collection technique uses observations, documentation, and interviews. The instrument used in observations is a study sheet, for documentation using a photo camera to document all the activities of the child during the activity and the interview using guidelines for interviews with teachers at the age of 4-5 to find out the conditions and problems faced. The results of research show that learning through pink tower arrangement can improve the ability of children aged 4-5 years in PAUD Sri Lestari Prefecture of Pontang district of Serang. The rate of success in children is increasing. The pre-cycle activity from an average of 64.10% increased from 9.94% in cycle I to 74.04% then increased again from 4.81% in Cycle II to 78.85%.